Interactions between PTCDI-C8 and Si(100) Surface - Katarzyna Lament; Miłosz Grodzicki; Piotr Mazur; Agata Sabik; Rafał Lewandków; Antoni Ciszewski (Crystals, 2023)
PTCDI-C8 molecules are vapor-deposited onto reconstructed Si(100)—(2 × 1) surface under ultra-high vacuum. X-ray photoelectron spectra reveal a bond formation between oxygen atoms of the molecules’ carboxylic groups and Si dangling bonds of the substrate. Following PTCDI—C8 film growth, ultraviolet photoelectron spectra show a drop in the HOMO level with respect to the Fermi level from 1.8 eV to 2.0 eV and a monotonic work function increase from 2.5 eV up to 3.3 eV. For a film thickness of 6.0 nm, a difference of 1.5 eV between the HOMO level of the film and the valence band maximum of the substrate is accomplished.